Reinterpreting Religious and Ethnic Music in Thailand - Surasak Jamnongsarn (IAHN-TP Palangka Raya, 2022)
Thailand is a society where different religious beliefs coexist peacefully. The main religions recognized by the Thai government are Buddhism, Islam, Christianity, Brahmin-Hinduism, and Sikhism. Each of these different religions does not make each religion teach people to behave differently, but it is well accepted that all religions teach us all to be good people. Traditional Thai Music (Dontri Thai) is diverse, reflecting a nation that people, culture, and history have shaped. Most Thai Muslims are of Malay descent, reflecting the common cultural heritage between Thailand's southern provinces shared with Malaysia. Thailand and Indonesia, the latter being popularly known by the former as chawa (Java), are two nations with long relationships since the traditional state era. Dvaravati, as The Mon Culture, was an ancient Mon kingdom from the 7th century to the 11th century, located in the region now known as central Thailand. Wai Khru ritual is a mixture of animistic, Brahmanist, and Buddhist rituals.